Caries Inhibition of Pit and Fissure Non Cavitated Lesions in Children by Low Level Lasers #x2013; A Clinical Study (Global Journal of Medical Research, 2020)
Background: The incipient non-cavitated carious lesion are characterized by subsurface dissolution which have potential to remineralize. Traditional remineralization protocols have varying results. An effective remineralizing protocol thus would be one which brings about a change in enamel crystal and makes it more resistant to acidic challenges of oral cavity. Material
Keywords: dental caries; non cavitated lesions; remineralization; wattage; time